Factors related to satisfaction with community-based home aging services in Shandong, China - Wang, Yujing; Zhang, Qi; Huang, Laigang; Zeng, Fanshuo (Frontiers in Public Health, 2024)
Purpose This study investigated the satisfaction of current community-based home care services and its factors in adults aged ≥60 years. Methods Using stratified cluster random sampling, we surveyed 1,494 older adults in Jinan and Qingdao, Shandong province, between 2021 and 2023. The baseline and satisfaction surveys were designed by our research team, and the questionnaires were conducted in the form of structured interviews. Kruskal-Wallis H-test and Logistic regression analysis were used to explore the influencing factors of satisfaction. Results The satisfaction was mainly affected by age (p = 0.007), marital status (p < 0.001), pre-retirement occupation (p = 0.003), economic source (p < 0.001), and mode of residence (p = 0.001) in the study of 1,494 older adults. Under the influence of multiple factors, the evaluation of older adults services, married [OR = 4.039, 95% CI: 1.176–13.877] were more inclined to be average, and their occupations were agriculture, forestry, animal husbandry, fishery, and water production workers [OR = 0. 237, 95% CI: 0.068–0.819] and production and transportation equipment operators and related personnel [OR = 0.153, 95% CI: 0.024–0.966] or [OR = 0.153, 95% CI: 0.029–0.820] tended to be more dissatisfied. Conclusion The satisfaction level of community-based home care services is relatively high among older adults, and it is mainly affected by factors such as age, marital status, pre-retirement occupation, source of financial resources, and mode of residence. Addressing the emotional needs of older adults, lowering the cost of aging, and integrating health care and aging seamlessly are among the ongoing challenges that we need to tackle.